An Analysis of Court Decisions Regarding Applications for Interfaith Marriage (Comparative Study of Decisions Number 131/Pdt.P/2021/PN Jkt.Sel and Number 122/Pdt.P/2020/PN.PTI) - Manalu, Gibson; Aryono, Aryono; Habib, Muhamad; Santoso, Aris Prio Agus (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
The emergence of differences in views regarding whether or not interfaith marriages are permissible in Indonesia because it has not been clearly regulated in the Marriage Law has led several people to apply for interfaith marriages. The aim of this research is to find out the legal basis and considerations of judges in handing down decisions on interfaith marriages in the District Court and the implications of the judge's decisions on these marriages. This research is normative juridical research which is based on several laws and regulations regarding marriage. The results of this research explain that (1) Decision Number 131/Pdt.P/2021/PN Jkt.Sel is an application for permission to register interfaith marriages which was granted by the South Jakarta District Court, where the judge thought there was a lack of explanation of the law because in The law does not expressly prohibit interfaith marriages. The judge's consideration in deciding this case was because he understood Article 2 paragraph 1 of the Marriage Law Number 1 of 1974, which states that marriage is valid according to the laws of each religion and belief. Meanwhile, determination Number 122/Pdt.P/2020/PN.PTI is an application for a marriage permit which was rejected because this application was deemed to contain formal defects so it could not be accepted (niet on vankelijke verklaard). (2) The legal implication of the decree being granted is that there is no problem because legally it is permissible to carry out interfaith marriages. This includes the relationship between husband and wife and their children, which is regulated in law and has permanent legal force. Meanwhile, the implication of a rejected decision regarding the validity of the marriage is that it is invalid and all legal consequences arising from the marriage are not recognized.